GAMBARAN HISTOPATOLOGI GINJAL TIKUS PUTIH (Rattus norvegicus) JANTAN YANG DIBERI INFUSA PARE LOKAL PULAU TIMOR - Maria Asti S.R Rafe; Cynthia D Gaina; Nemay A Ndaong (Jurnal Veteriner Nusantara, 2020)
Some of the chemical compounds in bitter melon fruit that acts as infertility for males, namely saponins, tannins, alkaloids, flavonoids and triterpenoids were able to reduce the number of spermatogenic cells. Renal excretory function in carrying out this gets tough task, because almost 25% of all blood flow to the two kidneys. The amount of blood flow to the kidney causes renal exposure to the material circulating in the circulation system is quite high, so that the toxic material will easily cause damage to the kidney tissue. This study aimed to determine the effect of dose delivery infusion of local bitter melon fruit on the island of Timor, East Nusa Tenggara against renal histopathology description of male white rat (Rattus norvegicus). The study was conducted in the 2 treatment groups, namely (P1) bitter melon infusion at a dose of 1250 mg/kgBB/day and (P2) bitter melon infusion at a dose of 2500 mg/kgBB/day. Each treatment group consisted of 6 rats administered for 48 days. Microscopic changes that occur in the kidneys of mice include glomerular congestion, atrophy of the glomerulus, tubular hemorrhage, necrosis of the tubules are composed of cells piknosis, Karyorrhexis cells, karyolysis cells and tubular protein deposits. The average glomerular damage and kidney tubules was higher in treatment P2 than P1 which indicates the ravages caused by high dose bitter melon infusion given to the treatment group P1 and P2 so that the chemical substances to be excessive and toxic, accumulate in the kidneys and cause damage to the kidneys